Evaluation of professional co-teaching practices - Arriagada, Carlos Roberto; Venegas, Natalie Gislaine; Calzadilla-Pérez, Oscar Ovidio (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Co-teaching is an internationally recognized strategy for its possibilities on teacherprofessional development and student learning, which involves considerable transformationsin the classroom. The Chilean Ministry of Education implemented this strategy through theSchool Integration Programs, pointing to it as a tool for improving the quality of education.Consequently, this article focuses on the evaluation of co-teaching practices through adescriptive and mixed study based on the interview and the focus group. The latter becamean occasion for understanding and reflecting on teachers’ pedagogical and curricularmanagement concerning co-teaching practices. From this evaluation, we identified bothdifficulties regarding time management for teaching preparation and the prevalenceof isolated work on the part of the classroom teacher and the differential educator. Theinstrumented improvement actions strengthened pedagogical leadership, teaching design,interpersonal relations, teacher professional development and student learning.